Response to “The promise and pitfalls: interpreting dual β-lactam success in Mycobacterium abscessus with caution” - Khalid M. Dousa; Robert A. Bonomo (ASM Case Reports, 2026)
ABSTRACT We read with interest the recent commentary (C. Mejia-Chew, ASM Case Rep 1:e00084-25, 2025, https://doi.org/10.1128/asmcr.00084-25 ) on our case report (M. Shimamura, B. Becken, J. Tansmore, M. Cristinziano, et al., ASM Case Rep 1:e00087-24, 2025, https://doi.org/10.1128/asmcr.00087-24 ). β-lactam therapy represents a mechanistically rational and clinically promising strategy for Mycobacterium abscessus , a pathogen with limited therapeutic options. Reported cases of β-lactam combinations illustrate how in vitro data, translational insights, and multidisciplinary clinical decision-making can inform salvage therapy in the absence of robust animal preclinical or clinical trial data. While challenges remain—including lack of standardized synergy testing, limited animal models, and complex polytherapy—these experiences underscore the importance of transparent reporting and provide the platform for rigorously evaluating β-lactam regimens.